2017
DOI: 10.1159/000485789
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological Findings of Follicular Dendritic Cell Sarcoma on Fine-Needle Aspiration Cytology

Abstract: Background: Follicular dendritic cell sarcoma (FDCS) is a rare neoplasm arising from follicular dendritic cells of germinal centers. The most common site of origin is lymph nodes and it may mimic a variety of tumors at that location, including carcinomas and sarcomas. Diagnosis is frequently missed on cytology as there are very few case reports describing the cytological characteristics of the lesion. Even on histology, a high degree of suspicion is required for an appropriate diagnosis. Case: A 60-year-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The diagnosis of FDSC on cytology fine needle aspiration (FNA) is challenging and misdiagnosis is common. Ojha et al, found that out of 15 FNA cases of FDCS, only three cases were diagnosed on cytology 9 . Ren et al, also showed similar findings in their study; only two of ten cases of FDCS were diagnosed on cytology, both of which had a prior known history (one was recurrent and the other was metastatic) 10 …”
Section: Discussionmentioning
confidence: 53%
“…The diagnosis of FDSC on cytology fine needle aspiration (FNA) is challenging and misdiagnosis is common. Ojha et al, found that out of 15 FNA cases of FDCS, only three cases were diagnosed on cytology 9 . Ren et al, also showed similar findings in their study; only two of ten cases of FDCS were diagnosed on cytology, both of which had a prior known history (one was recurrent and the other was metastatic) 10 …”
Section: Discussionmentioning
confidence: 53%
“…The diagnosis of FDCS may be challenging as its cytologic, histologic, and immunohistochemical features overlap with other entities in the differential diagnosis. A recent literature review of 15 FNA cases of FDCS is a testament to this, as it found that only three cases were diagnosed on cytology 14 . It therefore requires a high index of suspicion to prompt the appropriate workup with FDC‐specific markers.…”
Section: Resultsmentioning
confidence: 99%
“…Follicular dendritic cell sarcoma tumours are defined as histiocytic and dendritic cell tumours which develop in nodal and extranodal lymphoid tissue 3 . Physiologically, follicular dendritic cells serve as antigen‐presenting cells to B‐lymphocytes and provide structural support to lymphoid follicles.…”
Section: Discussionmentioning
confidence: 99%
“…The tumour cells are positive for CD21, CD23, CD35, clusterin, fascin and vimentin, and variably express EMA, S100 and CD68 immunostaining. A recent review of literature found 22 cytological reports of FDCS, and only five cases were diagnosed correctly on cytology, three of which were known cases of FDCS 3,6‐9 …”
Section: Discussionmentioning
confidence: 99%